The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1590/s1678-4634202248245243eng
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Knowledge and Pedagogical Practices

Abstract: This study deals with a research conducted with Brazilian and Portuguese teachers through an online course that aimed to design a continuing education approach that integrated basic, undergraduate and graduate education teachers, based on the “Seven Complex Lessons in Education for the Future.” To this end, it focused on the “lesson” that deals with error and illusion, from Edgar Morin’s perspective. The problem that guided the investigation sought to analyze participants’ perceptions about the influence of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The ease of just reproducing knowledge is due to the fact that the teacher, without pedagogical training, mastered and reproduced the discipline contents as he learned, known as knowledge transposition. 15 Engineering and technology schools continue to train professionals with little integration between disciplines (noninterdisciplinary way), which causes the student face difficulties relating them in a project development and execution. 16 In 2008, Tsividis conducted studies with electrical engineering students at Columbia University (New York, USA) and he concluded that engineering students need to overcome barriers in the educational process, such as:…”
Section: Teaching Of Engineering and Technology In Brazil And Worldwidementioning
confidence: 99%
See 1 more Smart Citation
“…The ease of just reproducing knowledge is due to the fact that the teacher, without pedagogical training, mastered and reproduced the discipline contents as he learned, known as knowledge transposition. 15 Engineering and technology schools continue to train professionals with little integration between disciplines (noninterdisciplinary way), which causes the student face difficulties relating them in a project development and execution. 16 In 2008, Tsividis conducted studies with electrical engineering students at Columbia University (New York, USA) and he concluded that engineering students need to overcome barriers in the educational process, such as:…”
Section: Teaching Of Engineering and Technology In Brazil And Worldwidementioning
confidence: 99%
“…The ease of just reproducing knowledge is due to the fact that the teacher, without pedagogical training, mastered and reproduced the discipline contents as he learned, known as knowledge transposition. 15…”
Section: Literature Reviewmentioning
confidence: 99%